2020
DOI: 10.1039/d0cp02730h
|View full text |Cite
|
Sign up to set email alerts
|

NMR parameters of FNNF as a test for coupled-cluster methods: CCSDT shielding and CC3 spin–spin coupling

Abstract: NMR shielding and spin-spin coupling constants of cis and trans isomers of FNNF have been determined to near-quantitative accuracy from ab initio calculations. The FNNF system, containing multiple N-F bonds...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…It is common to calculate chemical shifts including solvation , or in the gas phase. , The effect of including implicit solvation within the conductor-like polarizable continuum method , was evaluated in comparison to gas-phase results for a small set of methods (Supporting Information, Table S7). Interestingly, with all DHDF methods (DSD-PBEP86, revDOD-PBEP86, and revDSD-BLYP) the gas-phase results yielded smaller MADs than those using CPCM (CHCl 3 ) solvation.…”
Section: Resultsmentioning
confidence: 99%
“…It is common to calculate chemical shifts including solvation , or in the gas phase. , The effect of including implicit solvation within the conductor-like polarizable continuum method , was evaluated in comparison to gas-phase results for a small set of methods (Supporting Information, Table S7). Interestingly, with all DHDF methods (DSD-PBEP86, revDOD-PBEP86, and revDSD-BLYP) the gas-phase results yielded smaller MADs than those using CPCM (CHCl 3 ) solvation.…”
Section: Resultsmentioning
confidence: 99%
“…It is therefore fundamental to assess theoretical approaches capable of accurately reproducing SSCCs involving F. Despite the inherent better accuracy of a higher level of theory methods, density functional theory (DFT) still represents a popular choice, due to its favorable cost/performance ratio. DFT can be employed to study larger systems, as is often the case for organic molecules, while higher theory methods quickly become unfeasible. , However, the weakness of DFT lies in the nonuniversal description of the electron correlation. Consequently, the results are often largely dependent on the chosen functional, and benchmark studies need to be performed to establish the suitability of DFT methods for a given calculation.…”
Section: Introductionmentioning
confidence: 99%
“…Using these amplitudes, one can compute the occupiedoccupied and virtual-virtual blocks of the (perturbed) MP2 density matrix according to Eqs. ( 3), ( 4), (9), and (10). For the virtual-occupied block of the (perturbed) density matrix, insertion of the CD yields…”
Section: Cholesky Decomposition Of the Magnetic Two-electron Integral...mentioning
confidence: 99%
“…1 For the accurate computation of NMR shieldings it has been amply shown that the consideration of electron-correlation effects is essential. [2][3][4][5][6][7][8][9] In this respect, second-order Møller-Plesset (MP2) perturbation theory 10,11 has been shown to be very useful, 2,[12][13][14] even though highly accurate predictions of NMR shieldings, in particular when aiming at absolute shieldings, [15][16][17][18][19] require coupled-cluster (CC) treatments. 20 Nevertheless, as the calculation of relative NMR chemical shifts benefits from some error cancellation, MP2 computations can provide a very useful and reliable tool.…”
Section: Introductionmentioning
confidence: 99%